Integrated Transcriptomic and Proteomic Analyses Reveal CsrA-Mediated Regulation of Virulence and Metabolism in Vibrio alginolyticus - Bing Liu; Huizhen Chen; Kai Sheng; Jianxiang Fang; Ying Zhang; Chang Chen (Microorganisms, 2025)
Vibrio alginolyticus, a common Gram-negative opportunistic pathogen of marine animals and humans, is known for its rapid growth in organic-matter-rich environments. However, it remains unclear how it incorporates metabolic pathways in response to diverse carbon and nitrogen sources and rapidly alters gene expression. Increasing evidence suggests that post-transcriptional regulation by RNA-binding proteins and small RNAs (sRNAs) plays a crucial role in bacterial adaptation and metabolism. CsrA (carbon storage regulator A), a conserved post-transcriptional regulator in Gammaproteobacteria, is poorly characterized in Vibrio species. Using integrated transcriptomic and proteomic analyses, we found that CsrA alters the expression of 661 transcripts and 765 protein transcripts in V. alginolyticus, influencing key pathways including central carbon metabolism, amino acid metabolism and transport, quorum sensing, and bacterial secretion systems. Through directed CsrA-RNA EMSAs, we identified several direct mRNA targets of CsrA, including gltB, gcvP, aceE, and tdh, as well as secretion system components (tagH, tssL, yopD, and sctC). Notably, CsrA also directly regulates rraA, a key modulator of ribonuclease activity, suggesting a broader role in RNA metabolism. Our findings establish CsrA as a global regulator in V. alginolyticus, expanding the known targets of CsrA and providing new insights into its regulatory roles.